Qualifying Marks of Tampering With Evidence (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the qualifications of deliberate falsification of evidence. The collection of evidence, its examination and evaluation of criminal case materials are discussed. In addition, evidentiary requirements are defined and discussed. The norms of criminal law of some foreign countries that define criminal liability for deliberate falsification of evidence are also analyzed. The purpose of this study is that the most important condition for the correct classification of the crime of forgery of evidence (forgery) is - from similar crimes, abuse of power or authority (Article 205 of the Criminal Code of the Republic of Uzbekistan); Career fraud (Article 209 of the Criminal Code of the Republic of Uzbekistan); Production of documents, stamps, seals, forms, their counterfeiting, sale or use (Article 228 of the Criminal Code of the Republic of Uzbekistan); Falsification of the results of operational investigative activities (Article 2302 of the Criminal Code of the Republic of Uzbekistan); Bringing an innocent person to justice (Article 230 of the Criminal Code of the Republic of Uzbekistan); Various aspects of such crimes, such as giving false testimony (Article 238 of the Criminal Code of the Republic of Uzbekistan), are analyzed.